Analisis Framing Berita Demonstrasi Mahasiswa Semarang Terkait Kenaikan Harga BBM Pada TV Borobudur - Putri, Ayu Nur Irwinesia (Jurnal The Messenger, 2012)
The aim of the research to know news framing techniques and ideologies that used Borobudur Television in constructing news Semarang student demonstrations related increases in fuel prices.The theory base used in this research used framing analysis owned Zhongdang and Kosicki that consist of four devices of there: sintaksis, skrip, tematik and retoris. In addition, the concept of social construction, television news, and local television. The question in this research is how news framing techniques and ideologies in the news constructing student demonstrations.This research methodology used is descriptive qualitative. Analysis techniques used in this study is methode framing analysis with analysis models owned Zhongdang Pan and Gerald M. Kosicki. This study analyze the news script Semarang student demonstrations related increases in fuel prices broadcast by Borobudur Television period 20-31 March 2012.It is concluded that news framing techniques used in constructing news Borobudur Television student demonstration it is appropriate with the framing analysis owned Zhongdang because it containts four framing device. And ideologies that are used Borobudur Television appropriate with politics editorials that tends to reveal the reality according to what is happening on the ground.